In the pursuit of happiness all family leisure is not equal. Issue 4 (1st October 2016) - Melton, Karen K.; Zabriskie, Ramon B.
ABSTRACT: In the context of family leisure, individuals are more likely to achieve happiness when recreating with their families in predictable activities and in familiar environments. This hypothesis was tested by comparing three models predicting individual happiness. The three models were grounded in distinct frameworks of family leisure incongruity: (a) the null model – all family leisure is equal; (b) activity incongruity model – familiar versus unfamiliar family activities; and (c) location incongruity model – indoor-home, outdoor-home, community, and beyond the community. Analyses used a sample of 1502 individuals in 751 families from the U.K. Models were assessed using multi-level modelling. Overall, results indicated that in the pursuit of happiness all family leisure is not equal. The best predictors of happiness in the context of family leisure were quality family leisure time spent in familiar activities inside the home. Implications for today's families and future research are discussed.